The Concept Of Self Healing Perspective Of The Qur'an and Hadith - Muhammad Iqbal Ansari; Waluyo Satrio Adji; Raidah Raidah (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2022)
Lately, mental health is often discussed because the number of mental disorders in Indonesia has increased quite large in each period. Considering that alternative medicine is rarely used because of the rapid development of the times, this research has the aim of opening up people's minds to alternative medicine, including the Qur'an. This research is library research by analyzing several sources such as books, scientific articles and others. The independent variable in this study is self-healing, while the dependent variable is self-healing from the perspective of the Qur'an and Hadith.In the span of 14 centuries, healing with the Qur'an has become something that is already known to the Muslims. They treat all diseases with the Qur'an because they believe in the word of Allah SWT related to healing. In fact, ona narration explains that, the Prophet Muhammad SAW had meruqyah himself when he was sick by reading the letter al-Mu'awwidhatain, namely the letter al-Falaq and the letter an-Nas. Further research can be carried out by examining several suras, certain verses that are believed by Muslims to be very effective drugs against various diseases, especially mental illnesses.